1998
DOI: 10.1159/000057366
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β in Glomerular Disease

Abstract: Transforming growth factor-β (TGF-β) is an important cytokine in glomerular disease. Its major role may be to mediate extracellular matrix deposition, by both increasing the synthesis of matrix components and by reducing their degradation. Strong evidence supports the functional role for TGF-β in mesangial matrix expansion. However, TGF-β may also have other important functions in the glomerulus, including the regulation of cell proliferation, hypertrophy, and survival (apoptosis), as well as modulation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…However, hyperlipidemia did induce tubulointerstitial influx of macrophages/foam cells, presumably mediated by chemoattractants other than MCP-1. Studies have also indicated that macrophages from hyperlipidemic rats may be a major source for increased TGF-b expression [23,24], an important cytokine for mediating extracellular matrix deposition [53]. Our study also demonstrated a significant correlation between glomerular macrophage content and TGF-b expression.…”
Section: Discussionsupporting
confidence: 73%
“…However, hyperlipidemia did induce tubulointerstitial influx of macrophages/foam cells, presumably mediated by chemoattractants other than MCP-1. Studies have also indicated that macrophages from hyperlipidemic rats may be a major source for increased TGF-b expression [23,24], an important cytokine for mediating extracellular matrix deposition [53]. Our study also demonstrated a significant correlation between glomerular macrophage content and TGF-b expression.…”
Section: Discussionsupporting
confidence: 73%
“…TGF-b plays an important role in the pathogenesis of glomerular disease and mediates extracellular matrix deposition leading to glomerulosclerosis (Shankland and Johnson, 1998). However, TGF-b is also known to inhibit cell mitogenesis of a variety of cells including renal cells.…”
mentioning
confidence: 99%
“…Transforming growth factor-␤ (TGF-␤) is an important cytokine in renal disease (1,2). TGF-␤ mediates extracellular matrix protein accumulation, cell proliferation, and hypertrophy, and it also regulates the immune response.…”
mentioning
confidence: 99%